Entropy Analysis in Relativistic Heavy-Ion Collisions - Shakeel Ahmad; A. Ahmad; Anuj Chandra; M. Zafar; M. Irfan (Advances in High Energy Physics)
Entropy creation in multiparticle system is investigated by analysing the experimental data on ion-ion collisions at AGS and SPS energies and the results thus obtained are compared with those predicted by multiphase transport and correlation-free Monte Carlo models. Entropies produced in limited- and full-phase space are observed to increase with increasing beam energy. The entropy values, normalized to the maximum rapidity and plotted against pseudorapidity (bin width also normalized to the maximum rapidity), are found to be energy independent, exhibiting a kind of entropy scaling. Such scaling is observed in the full phase space as well as in the regions confined to the forward or backward hemispheres. The findings also reveal that there exist strong correlations amongst the particles produced in the forward and backward hemispheres around the midrapidity. These correlations are found to be of short range in nature, and the contributions from the long-range correlations seem to be absent. PACS numbers: 25.75-q, 25.75.Gz.